Safety and viability of a new format of thoracoepigastric flap for reconstruction of the chest wall in locally advanced breast cancer: a cross-sectional study - Ana Claudia Benjamim Burattini; Rafael Clark de Oliveira Piteri; Lia Fleissig Ferreira; Vagner Franco da Silveira Junior; Julia Broetto; Carlos Augusto Richter; Luiz Eduardo Felipe Abla; Luiz Henrique Gebrim (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Patients who undergo radical mastectomy with extensive tissue loss require a surgical procedure for rapid and simple closure of the lesion, with good skin coverage and minimal morbidity, to make them eligible for early complementary treatments. We evaluated the efficacy and safety of a new format of thoracoepigastric flap with patients in the Semi-Fowler position during surgery. We hypothesized that this procedure would achieve proper closure of large lesions and ensure the survival of the flap. METHODS: All consecutive patients who underwent radical mastectomy between 2009 and 2014 and had chest wall reconstruction were evaluated. The main outcomes evaluated were the viability of the flap and effectiveness of the surgical closure. RESULTS: During the study period, we operated on 29 patients with locally advanced (90%) or recurrent tumor (10%), and one patient was operated on bilaterally (total of 30 flaps). Of the study sample, 23 patients (79%) were at stage III and 6 (21%), at stage IV. The dimensions of the resected areas varied from 20 x 15 cm to 13 x 9 cm (average 15.5 x 11.6 cm). The dimensions of the thoracoepigastric flaps varied from 25 x 12 to 18 x 8 cm (average 21.3 x 10.4 cm). There were only 2 cases of dehiscence (7%), which resolved without surgical intervention, and one case of hematoma, which was drained surgically. One patient died on the eleventh postoperative day. CONCLUSION: Thoracoepigastric flaps were effective and safe, did not require the use of other flaps or skin grafting, and adequately closed the donor areas in all cases. All patients, except the patient who died, were eligible for complementary treatment one month after surgery.